Wireless Identification and Sensing with Surface Acoustic Waves - Reindl, Leonhard; Weigel, Robert (Recent Research Developments in Microwaves Theory & Techniques, 1999)
This paper surveys the operating principles of surface acoustic wave(SAW)-based wireless identification and sensing and the state-of-the-art performance by way of a few examples which include the remote measurement of temperature, pressure, electrical current, and humidity.
elib2cris::1512001600,reindl1999